Physician's prescription and pharmaceutical industry's influence - where have the ethics gone? - Zaeema Ahmer, (Journal of the Pakistan Medical Association, 2024)
The relationship between physicians and the pharmaceutical industry has evolved significantly over the years, raising concerns about ethical practices in medical prescribing. This article explores the multifaceted influence of pharmaceutical companies on physician behaviour, highlighting how marketing strategies, financial incentives, and promotional activities can compromise the integrity of clinical decision-making. Through a comprehensive review of the literature, the article examines the implications of inculcating ethics in undergraduate medical programmes, so future healthcare professionals understand the importance of making evidence-based decisions. Furthermore, this article calls for a critical evaluation of existing regulatory frameworks and advocates for stronger ethical guidelines to ensure that physician prescriptions are based solely on patient needs rather than external pressures from the pharmaceutical industry. Ultimately, it emphasizes the importance of restoring ethical standards in medicine to safeguard patient welfare and maintain the sanctity of the physician-patient relationship. Keywords: Physician’s prescription, pharmaceutical industry, Ethics.